Consumer Protection in E-Retailing in ASEAN - Ha, Huong (Issn Ser., 2021)
While many sectors have been badly affected by the COVID-19 pandemic, e-retailing is one of the booming sectors during this period. Actually, the e-retailing sector was already booming even before the global pandemic. Although e-retailing offers many opportunities for businesses and consumers, there are several issues associated with e-consumer protection. This book examines how consumers are protected on the online marketplace in the context of ASEAN countries. Specifically, this project: (i) Discusses the six issues of e-consumer protection (e.g., information about transaction, product quality, privacy, security, redress, and jurisdiction); (ii) Examines the policy/governance approach adopted by different sectors to address the issues of e-consumer protection; and (iii) Proposes a multisector governance framework for e-consumer protection. Three short case studies on Lazada in Singapore, Shopee in Vietnam, and Zalora in Malaysia are also included to illustrate how well-known e-retailers protect their e-customers. Overall, this book is interdisciplinary, including research on consumer protection, governance, management, and policy/regulation. It provides sources of information and knowledge which focus on both theoretical and practical aspects of e-consumer protection in ASEAN countries. Also, the roles from different sectors are examined to produce comprehensive findings and analysis of the governance process.